Sprinting characteristics of women's 100 meter finals at the IAAF World Championships Daegu 2011 - Park, S. -K.; Yoon, S.; Ryu, J.; Hwang, W. -S.; Kim, J. N.; Ha, S.; Koyama, H.; Mochida, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study analyzed the sprinting characteristics of the finalists during the women's 100 m event in the IAAF World Championships Daegu 2011 in order to provide important information to track and field coaches and athletes. Five high speed cameras (Casio, Japan) with a sampling frequency of 300 Hz were used to calculate the number of steps, step length, and stride frequency of the eight sprinters in the women`s final event. There was a tendency to show a better performance time with a high number of steps (p=0.13) and shorter stride length (p=0.14) among the eight sprinters. Furthermore, stride frequency and performance time were negatively correlated as a higher stride frequency had a positive impact on performance time (p=0.02). Based on the relationship between COM velocity and lower extremity joint angles, the 4 top ranked sprinters showed the different strategies to maintain a high COM velocity during the mid portion of the race.